Silver screen, Hasidic Jews : the story of an image - Hammerman, Shaina (Indiana University Press, 2018)
"Motivated by Woody Allen's brief comedic transformation into a Hasidic Jew in Annie Hall, cultural historian Shaina Hammerman examines the effects of real and imagined representations of Hasidic Jews in film, television, theater, and photography. Although these depictions could easily be dismissed as slapstick comedies and sexy dramas about forbidden relationships, Hammerman uses this ethnic imagery to ask meaningful questions about how Jewish identity, multiculturalism, belonging, and relevance are constructed on the stage and silver screen"--